Jury Verdicts Database for Cook County, Illinois, and All Counties in California, 1960-1984 - Dunworth, Terence ([Verlag nicht ermittelbar], 1994)
This data collection contains information on jury verdict civil cases in Cook County, Illinois, and all counties in California. The RAND Corporation's Institute for Criminal Justice began this study in the early 1980s in response to widespread public interest in the magnitude of dollar verdicts returned in civil cases. The goal was to record salient information found in court reporter publications to allow for a wide range of future research. Two such publications were chosen because of their favorable reputations and because they both dated back to 1960: the "Cook County Jury Verdict Reporter" of Chicago, Illinois, and "Jury Verdicts Weekly" of Santa Rosa, California. The collection of data for this study was conducted in two phases. Phase I included cases from 1960-1979, and Phase II coded cases from 1980-1984, including a small number of cases from 1985. In both phases, only cases in which a jury reached a definitive outcome (including deadlocked or hung juries) were included. In Phase I, only San Francisco County cases from the California reporter publication were included. In Phase II, all California counties were included. For all cases in Phase I, a Main Form was completed that included jurisdiction, court type, dates of incidents and trial, information about parties involved, trial occurrences, outcome of trial, awards, and fees. In addition to this Main Form, at least one of nine different case-type forms was completed: Common Carrier-Passenger Form, Dram Shop Form, Injuries on Property/Attractive Nuisance Form, Malpractice Form, Miscellaneous Form, Products Liability Form, Street Hazards/Highway Construction Form, Traffic/Pedestrian/Rider Form, and Work Injuries and FELA Form. These forms contained questions regarding the behavior of each party in the case and other characteristics and facts relevant to the case. A Jury Verdicts Form was completed for all cases in Phase II. This form picked up general case-level and defendant-specific data such as dates and length of trial, case outcome, original number of parties involved, and collapsing of multiple defendants into one case. For each plaintiff, a Plaintiff Information Form was filled out containing general plaintiff information such as losses claimed and the coder's assessment of the degree of the plaintiff's comparative negligence. This form also indicated which of the loss forms was coded for this plaintiff (only one loss form was completed for each plaintiff): Death Action, Personal Injuries, or Money Damages. Each form contained basic information about the outcome of the case, specific damages claimed by the plaintiff, and loss-specific data. Additionally, an Ancillary Action Form was completed for any associated claims that were adjudicated at the time of the main case, such as counter-suits by defendants. The questions on this form were the same as those on the main Jury Verdicts Form. Finally, this study includes an Integrated Jury Verdicts Database (Part 33) containing data from both phases to permit easier analysis of data from all years. This database contains five sections: (1) the basic trial information, which includes the trial dates and lengths, reporter source, and jurisdiction, (2) the main case information, which includes more detailed data about the case such as number of parties involved, case type, types of losses claimed, and total compensatory and punitive awards, (3) information about the first ancillary action, (4) information about the second ancillary action, and (5) a listing of all the forms used.